2022
DOI: 10.3389/fnagi.2022.1024496
|View full text |Cite
|
Sign up to set email alerts
|

Stroke-associated infection in patients with co-morbid diabetes mellitus is associated with in-hospital mortality

Abstract: Background and objectiveThe association between infection and acute ischemic stroke (AIS) with diabetes mellitus (DM) remains unknown. Therefore, this study aimed to explore the effect of infection on AIS with DM.Materials and methodsThe data of patients with AIS and DM were extracted from the Chinese Stroke Center Alliance (CSCA) database from August 2015 to July 2019. The association between infections [pneumonia or urinary tract infection (UTI)] and in-hospital mortality was analyzed. Logistic regression mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 46 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Impaired immune function during HG may be related to the increased susceptibility to infection and mortality in DM patients [ 45 ]. A previous study revealed that infection is an independent risk factor of in-hospital mortality for AIS patients with prior-stroke DM [ 46 ]. In this study, results obtained from multivariate analysis of SAP predictors among DM patients were in agreement with the results of patients with HG during AIS as the majority of patients with HG during AIS had prior-stroke DM.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired immune function during HG may be related to the increased susceptibility to infection and mortality in DM patients [ 45 ]. A previous study revealed that infection is an independent risk factor of in-hospital mortality for AIS patients with prior-stroke DM [ 46 ]. In this study, results obtained from multivariate analysis of SAP predictors among DM patients were in agreement with the results of patients with HG during AIS as the majority of patients with HG during AIS had prior-stroke DM.…”
Section: Discussionmentioning
confidence: 99%